Kegiatan penyediaan pelayanan perpustakaan dalam layanan unggah mandiri tugas akhir: studi kualitatif layanan unggah mandiri tugas akhir di Telkom University Open Library - Rozaanah Khoerunnisa; Sukaesih Sukaesih; Saleha Rodiah (Faculty of Communication, Padjadjaran University, 2022)
This study was conducted against the background of the emergence of news regarding the disposal of a student's final scientific assignment by one of the university libraries in Indonesia which at that time had become the focus of attention. In addition, the developments that occurred in the handover service for students' final scientific assignment also became the background for this study. This study aims to determine the technical service activities consisting of collecting, processing, disseminating, and preserving that are carried out by the library in supporting the implementation of the final assignment self-upload service at Telkom University Open Library. The research method used in this study is a descriptive qualitative method. Data was collected using observation, interviews, and documentation techniques. The research informants are library staff of Telkom University Open Library. The validity of the data was tested by triangulation techniques and source triangulation. Data analysis was carried out by data reduction, data presentation, and concluding. The results of the study provide information that technical service activities in the final assignment self-upload service at the collecting stage are carried out by library staff by verifying documents and the “Surat Bebas Kewajiban Perpustakaan” (Library Liability Free Letter) administrative requirements which consist of free of library loans and fines, and donating a book following the provisions. Processing activities are carried out by the processing staff by inputting document catalogs, inputting journal articles of the final project to Tel-U e-Proceeding, and making FlipBooks. Disseminating activities are carried out by providing final project collections and Tel-U e-Proceeding. Information dissemination activities are carried out by holding literacy class and distributing infographic content with the aim of attracting use from library users. Preserving activities are carried out by making metadata backups, document backups in docx and PDF format on external hard disk, and maintaining library websites.